Agronomic characteristics of corn for silage under nitrogen and potassium levels by covering fertilization - Neumann, Mikael; Horst, Egon Henrique; Dochwat, André; Leão, Guilherme Fernando Mattos; Carneiro, Murilo klosovski; Mello, Richard Paglia de (Scientia Agraria Paranaensis, 2017)
The objective was to evaluate the productivity, morphological and chemical composition, in addition to the economic viability of the corn crop (Zea mays L.) for the production of silage under different levels of nitrogen and potassium fertilization in coverage. Treatments consisted of four coverage levels: T1 (217 kg ha-1 N + 137 kg ha-1 K2O); T2 (295 kg ha-1 N + 163 kg ha-1 K2O); T3 (374 kg ha-1 N + 190 kg ha-1 K2O); and T4 (452 kg ha-1 N + 216 kg ha-1 of K2O). It was found that the fertilization level had no effect (P > 0.05) in the parameters related to plant height, height of the first insertion spike and grain production, however, higher (P < 0.05) dry biomass production was obtained with 374 kg ha-1 N + 190 kg ha-1 coverage K2O (32,346 kg ha-1). For TDN and FRV parameters, higher values (P < 0.05), respectively, were observed for 374 kg ha-1 N + 190 kg ha-1 K2O (71.30% and 132.0) and 452 kg ha-1 N + 216 kg ha-1 K2O (71.14% and 131.6) coverage fertilization. However, the lower level had the lowest cost per ton of TDN ha-1 produced. Overall, the P30R50HY corn hybrid showed high productivity and adequate nutritional characteristics when grown in minimum coverage level fertilization.